Angioplasty mimetic stented ion transport channels construct durable high-performance membranes. Issue 16 (3rd April 2019) - Shehzad, Muhammad A.; Liang, Xian; Yasmin, Aqsa; Ge, Xiaolin; Xiao, Xinle; Zhu, Yuan; Ge, Zijuan; Wang, Yang; Wu, Liang; Xu, Tongwen
Abstract : Stenting stabilizes the ion transport channels which hold excess water and boosts ion permeation, thus overcoming the current stability–efficiency tradeoffs. Abstract : Highly ion permeable channeled polymeric membranes are desirable for water treatment, energy transformation, and energy storage devices such as electrodialyzers, fuel cells, and batteries, respectively. However, excessive swelling per unit water of solvation and reduction in ion permeation efficiency of the conventional ion transport channels dictate the need for effectual unconventional channel designs. In this context, we hereby propose angioplasty mimetic "stented ion transport channels (SITCs)" to overcome the stability–efficiency tradeoff in the current channeled membranes. The semi crystalline polyaniline stents enable systematic self-assembling of the ion exchange sites to form electrostatically locked stent walls of almost 2.8 nm thickness (negligible peak broadening in SAXS spectra of the dry and wet stented membranes). The stents help hold the channels open, and thus decrease their swelling degree (35% less). Moreover, the hydrophilic PANI stents hold more water (19% higher) to keep the ions hydrated during transportation and boost ion permeation (2.33× higher) compared with the non-stented sulfonated polyphenylene oxide membranes. Besides, the stented membranes offer an almost 3× wider window for execution of electro-chemical processes, 2.3× less resistance, and 75% higher saline-water treatment performance than state-of-the-art Neosepta CMX membranes (ASTOM, Japan).